Poverty Alleviation Programme and Poverty Reduction in Anambra State. Evidence from Women Business Ownership - Ozoh, Joan N.; Metu, Amaka G.; Stephen M. , Chukwuka; Madueke, Chinwe (Advances in Social Sciences Research Journal, 2020)
The fight against poverty is one of the key components of the development of any country. If the percentage of poor people is high, there will be slow development. The government policies and program such as YOUWIN, Better Life is aimed at encouraging entrepreneurship and supporting women into business. Despite these efforts, poverty incidence still increases among women in micro business. This study examined government alleviation programs and dimension of poverty among women into micro business in Anambra state, Nigeria. It is a descriptive survey research. Probability and non- probability sampling technique were employed in which the samples were drawn using multi-stage sampling and purposive sampling technique. Questionnaire was used as an instrument for data collection. Data were analyzed using descriptive statistics, chi-square and Multidimensional Poverty Index (MPI). The findings of this study showed that most women participating in micro business are not aware of poverty reduction programs and do not have access to such programs. The study also found out that most of the women still experience hardship, no access to infrastructure, no good health care system and low standard of living which indicates that poverty has not reduced. The study recommended among others that the government should target its reduction policies towards the multidimensional indicators (good infrastructure, good health care system etc.) of poverty in order to eradicate poverty.